Marketing of unproven stem cell–based interventions: A call to action - Sipp, D; Caulfield, T; Kaye, J; Barfoot, J; Blackburn, C; Chan, S; De Luca, M; Kent, A; McCabe, C; Munsie, M; Sleeboom-Faulkner, M; Sugarman, J; et al. (American Association for the Advancement of Science, 2017)
Commercial promotion of unsupported therapeutic uses of stem cells is a global problem that has proven resistant to regulatory efforts. Here, we suggest a coordinated approach at the national and international levels focused on engagement, harmonization, and enforcement to reduce the risks associated with direct-to-consumer marketing of unproven stem cell treatments.